Anti-Inflammatory Activity of Ethanol Extract of Turmeric Rhizome (Curcuma Longa Linn) Male White Mice Pepper Induced Caragenan - Nur Ulina M. Br. Turnip; Sefrini Ois Lasmaria Pasaribu (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Inflammation is the body's natural response to tissue injury caused by internal or external stimuli, with the aim of neutralizing the agent causing damage and repairing injured tissue. Initial treatment of inflammation is generally done by eliminating local triggering factors, such as pain relievers through the use of chemical drugs. However, this therapy often causes unwanted side effects. The use of natural ingredients that have anti-inflammatory activity is a safer alternative than modern drugs. Objective: to determine the anti-inflammatory effect of ethanol extract of turmeric rhizome (Curcuma longa L.). Method: using a model of edema on the soles of the feet of male white mice induced by 1% carrageenan. A total of 24 mice were divided into 6 treatment groups, one group was not given treatment as a comparison, three groups received doses of ethanol extract of turmeric rhizome (100, 200, and 300 mg/kgBW), one negative control (Na CMC 0.5%), and one positive control (6.5 mg/kgBW Na diclofenac). Results: showed that after carrageenan induction, all test groups experienced a progressive decrease in inflammation levels from the 60th to the 360th minute. After the extract dose groups of 100 mg/kgBW, 200 mg/kgBW, 300 mg/kgBW, and Na diclofenac, the Na CMC group had the highest percentage of inflammation at the 120th minute. The Na diclofenac group showed the highest percentage of inflammation inhibition, followed by extract doses of 300, 200, and 100 mg/kgBW. In contrast to the Na CMC group which did not show anti-inflammatory activity, these data indicate that the ethanol extract of turmeric rhizome at a dose of 300 mg/kgBW has the highest anti-inflammatory efficacy after Na diclofenac, followed by doses of 200 mg/kgBW and 100 mg/kgBW. Conclusion: turmeric rhizome extract has the potential to reduce inflammation in the soles of mice's feet.